Modification of dolomitization on reservoir spaces in reef–shoal complex: A case study of Permian Changxing Formation, Sichuan Basin, SW China - Zhang Qiang; Liu Lizhi; Song Honglu; Jin Chaosu; Qiao Na; Qi Lin (Open Geosciences)
The porosity of the reef–shoal complex increases with the increase of dolomite content, and it is worth investigating whether dolomitization leads to the formation of new pores or maintains the original porosity. The reef–shoal complex of the Permian Changxing Formation in the Sichuan Basin is selected to reveal the modification effect of dolomitization on the reef–shoal complex. As important reservoirs of hydrocarbons and carbon dioxide, reef–shoal complexes are composed of grainstone and framestone on both sides of the Kaijiang-Liangping Trough during the Late Permian. The difference in the development degree of sparry calcite cement determines whether the framestone on both sides of the Trough undergoes dolomitization or not. When the Mg2+ supply is insufficient, the dolomitization fluid prioritizes the replacement of the lime mud matrix. When the Mg2+ supply is sufficient, the reef-building organisms and bioclastic grains are completely replaced by dolomite. Statistical results show that when the dolomite content increases from 0 to 40%, there is no significant change in porosity. When dolomite content increases from 40 to 60%, the porosity gradually increases slightly. When dolomite content exceeds 60% and continues to increase, the porosity increases sharply. For reef–shoal complex reservoirs, dolomitization did not lead to the formation of new pores, but effectively preserved primary intergranular pores and freshwater leaching-induced pores. The porosity increases with the increase of dolomite content, partly due to pore preservation and partly due to the more effective anticompaction (and pressure solution) effect of dolomite compared to calcite, reflecting the overall effect of dolomite pore preservation. Although early freshwater leaching played a positive role in the formation of dolomite reservoirs, the preservation effect of dolomite pores contributes more to the current porosity and permeability of reservoirs, resulting in the highest quality reservoirs of reef–shoal complexes often developing at a certain distance below the exposed surface, and the best reservoir is dolomite in the upper part of the reef–shoal complexes, rather than dolomite interval located at the top.